Morphogenesis of Rosa hybrida Linn var. Christian Dior in vitro - Mat Taha, Rosna; Awal, Asmah (Malaysian Journal of Science (MJS), 1994)
In vitro studies on morphogenesis ofan ornamental plant, Rosa hybrida Linn. var. Christian Dior were carried out on explant sources such as leaf, stem and shoot. Various plant hormones such as BA (6-Benzylaminopurine), NAA (ct -Naphthaleneacetic acid) and TDZ [1-phenyl-3-(1,2,3,-thiadiazol-5-yl) urea] were used to initiate cultures and to observe the morphogenetic response of the species. Different concentrations of sucrose and pH were tested in order to obtain plant regeneration. Multiple shoots were obtained from shoots and stems cultured on MS supplemented with 2.0 mg/ L BA + 0.1 mg/L NAA and 4.0 mg/L BA